Atividade biológica do óleo essencial de Cymbopogon nardus e do fitoconstituinte citronelal sobre cepas de Candida envolvidas com infecções peri-implantares - Trindade, Leonardo Antunes (2014)
The study aimed to evaluate the biological activity of the essential oil of Cymbopogon nardus and citronellal phytochemical on Candida strains, checking the possible inhibition of adhesion to dental implants and cover screws. Initially, a screening was performed by the disk diffusion technique in Sabouraud Dextrose Agar (SDA) for the essential oils of Cinnamomum camphora (White Camphor), Melissa officinalis (Lemon Balm), Ocimum basilicum (Basil) and Cymbopogon nardus (citronella), as well as phytochemicals alpha pinene, citral, citronellal and carvacrol. After screening, the essential oil of C. nardus and citronellal were selected because they displayed significant antifungal activity. Then, essential oil was analyzed by Gas chromatography mass spectrometry (GC-MS). Subsequently, were determined MIC and MFC of essential oil and citronellal against 12 strains of Candida and tests of inhibition of adhesion to dental implants and cover screws, using the MIC of substances evaluated, followed by analysis on a Scanning Electron Microscope (SEM). Assays were performed in triplicate and chlorhexidine and nystatin were used as positive control. The data were analyzed on the software GraphPad Prism 4. Analysis of variance (ANOVA) with Tukey s post-test was carried out, with a confidence interval of 95%. The GC-MS analysis of the essential oil identified the major substance as citronellal terpenoid. The essential oil, citronellal, chlorhexidine and nystatin able to inhibit 100% of the strains was 64 μg/mL, 512 μg/mL, 64 μg/mL, 32 μg/mL, respectively. The essential oil inhibited the adhesion of C. albicans in the dental implants and cover screws (p <0.001). Citronellal only inhibited the growth of the strain in dental implants (p <0.001) with no significant results in the cover screws (p> 0.05) compared to the growth control. We conclude that the essential oil of C. nardus and citronellal have antifungal activity and are able to inhibit the in vitro adherence of C. abicans.